Pengaruh Implementasi Konsep Kaizen Terhadap Kinerja Karyawan Pt Adaro Indonesia Di Divisi External Relations - Aliza Rahmi Saidah; Tinik Sugiati (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
This research aims to analyze the influence of Kaizen which consist of seiri (X1), seiton (X2), seiso (X3), seiketsu (X4) dan shitsuke (X5) as independent variables to employee performance (Y) as dependent variable in External Relations Division at PT Adaro Indonesia. The method of this research used questionnaire with 83 employees of External Relations Division at PT Adaro Indonesia as a sample. The variables measurement uses Likert’s Scale technique with weighting scale from 1 to 5. To find out the correlation among variables X1, X2, X3, X4 and X5 towards Y uses statistical technique of correlation analysis, multiple linear regression and to test the significance rate uses F test and t test processed with SPSS program. In the findings of this present research shows that seiri (X1) and shitsuke (X5) as Kaizen were found to have a positive significant relationship with the employees’ performance. While seiton (X2), seiso (X3) and seiketsu (X4) have no significant relationship with the employees’ performance.